The Effectiveness of Mimosa Extract, Garlic, and Galangal Against White Rust Disease (Puccinia Horiana Henn.) in the Nursery Plants of Chryns (Chrysanthemum SP.) - Montong, Bernadeth V.; Ratulangi, Max M.; Kalrengsang, Sandra O. K. (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
Chrysanthemum (Chrysanthemum sp.) is an ornamental plant that produces flowers that have high economic value. Chrysanthemum flowers have the potential to be developed because they are in great demand by the public in terms of beautiful shapes and colors. One of the important stages in chrysanthemum cultivation is seeding. The main problem in chrysanthemum farming is the attack of white rust caused by a fungus (P. horiana) starting from seedling to harvesting. The use of plant extracts as alternative pesticides has many advantages and benefits. Plants that have the potential to be used as botanical pesticides include mimosa, garlic and galangal. This study aims to determine the effectiveness of giving the mimosa, garlic and galangal extracts in chrysanthemum plant nurseries to suppress white rust disease caused by the fungus P. horiana. This research was carried out using an experimental design, namely a completely randomized design (CRD) which consisted of 4 (four) treatments and 4 replications, namely K (control), P1 (20% mimosa extract), P2 (20% garlic extract), and P3 (20% galangal extract). Based on the results of observations of the symptoms of white rust (P. horiana) the upper surface of the leaves at first in the form of yellow spots which gradually changed color to dark brown, then on the lower surface of the leaves can be seen the presence of pustules that are pink, and long Over time the pustules will get bigger and then turn white. The highest percentage of attacks was in control (K), 10.08%; the garlic extract treatment at 20% (P2) at 4.27%, then followed by the 20% galangal extract treatment (P3) at 3.33%, and the mimosa extract treatment 20% (P1) 0.96%. The results showed that the use of extracts of Putri malu, garlic and galangal was able to suppress white rust disease (P. horiana) in chrysanthemum plant nurseries, with the best treatment in suppressing white rust disease (P. horiana) which was mimosa extract 20% (P1 ) with attack percentage: 0.96%, followed by galangal extract (P3): 3.33% and garlic extract (P2): 4.27%. In accordance with the results of the research that has been carried out, it is necessary to carry out further research on the use of Mimosa Extract, Garlic and Galangal against white rust (P. horiana) in chrysanthemum plant nurseries with higher concentrations and in other varieties of chrysanthemum seedlings.